Exploring speciality preferences and the influencing factors among undergraduate medical students at University of Kufa - Iraq: a questionnaire-based cross-sectional survey - Amjed Hamid Obaid Al-Jaeed ,; Yosif Mohammed Hasan Jawad Al-Rammahi ,; Mohammed Albaqer Abbas Baqer Mawash ,; Hameed Kareem Shaalan Al-Hadrawy,; Basima Shamkhi Jabbar Al Ghazali, (Journal of the Pakistan Medical Association, 2021)
Objective: To explore Kufa medical students’ preferences of carrier specialization and to investigate the factors that influence their choice of specialty. Methods: By using a non-probability convenience sampling technique, a cross-sectional study was performed on (566) medical students from the second-to-sixth-year in University of Kufa, from the 27th of January to the 21st of February 2019 to study the factors that affect the choice of specialties in undergraduate medical students. An anonymous, structured, self-administered questionnaire was handed out to the students and consisted of three sections covering demographic data, the preferred specialty, and the cause behind selecting the specialty. Data analysis was performed using the statistical package for social sciences (SPSS) version 25 for windows. Results: Cardiology was the most chosen specialty 55 (9.7%) followed by Pediatrics 46 (8.1%) and Dermatology 45 (8.0%). Additionally, 40 (7.1%) students haven’t decided their specialties yet. The most chosen factors in a descending fashion were "My Passion" which was chosen by 427 (75.4%) students, followed by "income" 67 (11.8%), "less on-call duties" 51 (9.0%), "mentor inspiration" 46 (8.1%), "family member inspiration" 34 (6.0%), "reputation" 22 (3.8%), "less competition" 15 (2.6%), and "number of residency years" 8 (1.4%). Conclusion: Being passionate about or having a keen interest in the selected speciality were the major influencing factors for students to select their future speciality. However, male students' choices based mainly on the “income” and “reputation” of the field, while females opted to choose “less on call duties” more than males. Continuous...